2002
DOI: 10.1051/0004-6361:20011803
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale star formation in galaxies

Abstract: Abstract. The identification of young star groupings (YSG) in the three spiral galaxies NGC 3377A, NGC 3507, NGC 4394 is obtained by mean of the statistical method described in Paper I. We find 83, 90, 185 YSGs, respectively. An identification map of YSGs, as well as their size distribution, their B-luminosity function and their surface luminosity density radial behaviour are presented and compared. These data, in addition to those in Paper I, constitute a first sample suitable for seeking correlations among p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This has recently been supported by high resolution spectroscopic H I-measurements of Huchtmeier et al (2003), who find a double peaked profile for this galaxy which is typical for spirals. The H I intensity maps of Simpson & Gottesman (2000) show a ring-shaped distribution of the gas which is surrounding the bulk of the optical body and is correlated with the young star groups discovered by Vicari et al (2002). Knezek et al (1999) also measured the H α luminosity of UGC 5889 and found a relatively low value of L H α ∼ 2.6 × 10 38 ergs s −1 , which is about ten times lower than the average H α luminosity in the sample of quiescent dwarf spiral galaxies studied by van Zee et al (1997).…”
Section: Introductionmentioning
confidence: 58%
“…This has recently been supported by high resolution spectroscopic H I-measurements of Huchtmeier et al (2003), who find a double peaked profile for this galaxy which is typical for spirals. The H I intensity maps of Simpson & Gottesman (2000) show a ring-shaped distribution of the gas which is surrounding the bulk of the optical body and is correlated with the young star groups discovered by Vicari et al (2002). Knezek et al (1999) also measured the H α luminosity of UGC 5889 and found a relatively low value of L H α ∼ 2.6 × 10 38 ergs s −1 , which is about ten times lower than the average H α luminosity in the sample of quiescent dwarf spiral galaxies studied by van Zee et al (1997).…”
Section: Introductionmentioning
confidence: 58%
“…6 shows a bimodal size distribution of star formation regions of Level 2 and lower. Bimodal size distributions with a secondary peak at d = 150 − 300 pc were found for 'associations' in SMC (Battinelli 1991), M31 (Magnier et al 1993), NGC 2090, NGC 2541, NGC 3351, NGC 3621 and NGC 4548 (Bresolin et al 1998, NGC 1058 and UGC 12732 (Battinelli et al 2000), NGC 300 (Pietrzyński et al 2001), NGC 3507 and NGC 4394 (Vicari et al 2002), NGC 7793 (Pietrzyński et al 2005). Pietrzyński et al (2005) named such 'associations' 'superassociations'.…”
Section: Discussionmentioning
confidence: 98%
“…where R 3 is the projected distance to the third nearest neighbour galaxy, given in Mpc. Among the galaxies in our sample with the highest values of Σ A 3 , NGC 4548 and NGC 5850 are known to host signs of recent interactions with a nearby companion (e.g., Higdon et al 1998;Vollmer et al 1999), and NGC 4394 likely belongs to the M 85 subgroup of the Virgo Cluster (e.g., Vicari et al 2002).…”
Section: Sample and Datamentioning
confidence: 96%